Feasibility of Urban Nutrition Gardening Concept Combined with Maternal Infant and Young Child Nutrition Training in Kathmandu and Lalitpur during 2016 and 2017. - Uprety, Sophiya. (Tufts University. Tisch Library., 2019)
This poster points out that Urban Nutrition Gardening is indicated to be a feasible concept to integrate with MIYCN collaboration with ongoing gardening urban municipalities.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy